New brazilian predaceous midges of the genus Monohelea Kieffer, and redescription of M. guaimiesi (Diptera: Ceratopogonidae) - Maria Luiza Felippe-Bauer; Gustavo R. Spinelli (Memorias do Instituto Oswaldo Cruz, 1991)
Two new Brazilian species of Monohelea Kieffer, M. affinis and M. roraimensis are described and illustrated, and a redescription of M. guiaimiesi Lane & Wirth is given.